Quantifying and categorizing development paths of poverty-elimination counties in China: Based on the perspective of population-land-industry - Qianxi Zhang; Zhi Cao; Sixin Su; Xuanchang Zhang (Geography and Sustainability)
China has achieved the poverty reduction goal of the United Nations 2030 Agenda for Sustainable Development 10 years ahead of schedule, contributing significantly to global poverty reduction. Despite extended efforts in poverty elimination, there is a lack of quantitative studies categorizing and comparing poverty-elimination counties (PECs) based on their processes. This study proposes an innovative framework for analyzing PECs’ development paths from the perspective of population-land-industry (PLI). We quantify the PLI matching degree of PECs in China during the critical phase of the battle against poverty through a multivariate matching model, classify PECs via K-means clustering according to the consistency in PLI matching degree evolution, and summarize the typical development patterns of PECs. Results indicate that the PLI matching degree of PECs in China increased substantially from 2015 to 2020, particularly in eastern areas, while the western region, including the Qinghai-Xizang Plateau and southwestern Xinjiang, shows untapped potential for improvement. Five types of PECs are identified, with the majority (30.1 %) showing sustained moderate PLI matching and a minority (9.6 %) experiencing long-term PLI mismatch. Industry is the shortfall of various PECs, and effective strategies to facilitate all types of PECs include the development of emerging businesses and the expansion of secondary and tertiary industries. Additionally, enriching rural labor force and increasing farmland use efficiency are essential for optimal PLI matching and positive interaction, ultimately ensuring poverty elimination and sustainable development.